Factors affecting fatigue progression in multiple sclerosis patients - Dima Machtoub; Callie Fares; Hassan Sinan; Moustafa Al Hariri; Rim Nehme; Joelle Chami; Ronny Joukhdar; Raya Tcheroyan; Salim Adib; Samia J. Khoury (Scientific Reports)
Abstract Fatigue is one of the most prevalent and disabling symptoms among patients with MS, but there is limited research investigating the longitudinal determinants of fatigue progression. This study aims to identify the sociodemographic, behavioral and clinical characteristics, and therapeutic regimens that are correlated with worsening fatigue over time in patients diagnosed with MS. This is a retrospective chart review of 483 patients. The primary outcome was a change in the Modified Fatigue Impact Scale-5 (MFIS-5) score from first to last visit during the study interval, from November 2018 to November 2020. The study found that progressive MS subtypes, worsening depression, worsening pain, use of antidepressants, and use of fatigue medications were significantly associated with negative fatigue outcomes. Meanwhile age, sex, smoking frequency, use of pain medications, disease-modifying therapies, BMI, number of relapses, visits, steroid courses, and co-morbidities did not show an association. The clinical characteristics associated with worsening fatigue include progressive MS subtypes, worsening depression, worsening pain, use of antidepressants, and use of fatigue medications. Further studies are needed in order to elucidate a causal relationship and determine whether the management of fatigue in patients with MS should include interventions that address the aforementioned variables to optimize patient care and improve quality of life.